2022
DOI: 10.1038/s41598-022-17049-7
|View full text |Cite
|
Sign up to set email alerts
|

Physiological measurements in social acceptance of self driving technologies

Abstract: The goal of the present study is to examine the cognitive/affective physiological correlates of passenger travel experience in autonomously driven transportation systems. We investigated the social acceptance and cognitive aspects of self-driving technology by measuring physiological responses in real-world experimental settings using eye-tracking and EEG measures simultaneously on 38 volunteers. A typical test run included human-driven (Human) and Autonomous conditions in the same vehicle, in a safe environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
1
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
(62 reference statements)
2
4
1
4
Order By: Relevance
“…The most notable result of the EEG analyses showed a signi cant difference in frontal alpha asymmetry for human and self-driving conditions suggesting lower values during the novel experience of the vehicle navigating by itself. This replicates previous ndings that participants preferred the situation when the vehicle was driven by a human driver over the self-driving mode [15]. As it was hypothesized earlier, lack of perceived control over the movement of the vehicle [30,31] is a possible explanation of the observed disparity here.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The most notable result of the EEG analyses showed a signi cant difference in frontal alpha asymmetry for human and self-driving conditions suggesting lower values during the novel experience of the vehicle navigating by itself. This replicates previous ndings that participants preferred the situation when the vehicle was driven by a human driver over the self-driving mode [15]. As it was hypothesized earlier, lack of perceived control over the movement of the vehicle [30,31] is a possible explanation of the observed disparity here.…”
Section: Discussionsupporting
confidence: 91%
“…We recorded and analyzed EEG, eye movement, head movement and blinking frequency in relation to driving conditions and road events. Despite some contrasts, our results were comparable to earlier ndings [15]. The expanded design allowed us to see possible interactions between the effect of driving modes and the experienced events.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…As technological innovations change and grow quickly, it appears reasonable to expect that individuals who can flexibly adapt to their environment and to new situations are more open to accepting AV technology. When participants were passengers in an AV driven by a human driver or in autonomous mode, Palatinus et al [ 58 ] found that the eye movement pattern of individuals with higher level of Ego-resilience was not affected as greatly by the difference between human and autonomous driving conditions compared to those with lower level of Ego-resilience. This suggests that a higher level of Ego-resilience was accompanied by lower alertness or arousal when the vehicle was driving without human control, which might be explained by better and more flexible adaptation to the unfamiliar driving situation.…”
Section: Introductionmentioning
confidence: 99%